Implementation of Crumb Rubber Modified Binder for Qatar Local Roads Construction Projects - Nunoo, Charles N.; Al-Tamimi, Saoud Ali (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
The continuous increase in the pile up of used vehicle tires in Qatar poses a challenge contributing to potential environmental pollution problems. The magnitude of this problem can be drastically reduced by processing and recycling these tire wastes into crumb rubber, obtained from grinding up whole scrap tires, and incorporating into conventional asphalt binder to produce Crumb Rubber Modified Binder (CRMB) for asphalt mixes used in pavement construction. Asphalt mixtures which incorporates crumb rubber have been used in different parts of the world, notably USA since the 1960s, ostensibly to solve the associated environmental problems, but with added advantages of improving the overall performance of the asphalt pavement in terms of rutting and crack resistance, increased flexibility and durability. In 2018, the Roads Project Department (RPD) in collaboration with the Quality and Safety Department (QSD) of the Public Works Authority (PWA) in Qatar, undertook a demonstration project which utilized CRMB in the wearing course, in lieu of Polymer Modified Binder (PMB) originally proposed. Preliminary results from this project showed an encouraging prospect for adopting Crumb Rubber Modified Binder technology on local road projects, and eventually on all other roads in Qatar. Consequently, it became imperative for a tentative specification to be quickly put together for use by suppliers and contractors to achieve this goal. The preliminary results of this demonstration project are promising and the ensuing crumb rubber and CRMB guidelines have been useful.